'Learning to be Zen': women travellers and the imperative to happy. Issue 1 (2nd January 2017) - Falconer, Emily
Abstract: This paper follows the emotional management of lone, independent women travellers as they move through tourist spaces, based on my doctoral research Embodiment and Emotion in the experiences of independent women tourists (2009–2012). Specifically, this paper will focus on 'gendering happiness' by arguing that women travellers are significantly compelled to feel and display characteristics of happiness, humour and 'learning to be Zen' in order to be successful travellers. The imperative to become, and remain, happy and humourous in the face of embodied, emotional and gendered constraints is a key feature of women's reflections of their travelling experiences, mirroring the recent emergence of literature into happiness and positive thinking within feminist theory. Negotiating 'bad' emotions provides a powerful insight into the perceptions of women travellers; to remain happy can mask problematic power relations and other forms of resistance. This is not to say that emotional negotiation is not partly a form of effective resistance, rather, I wish to make room for the freedom to be unhappy and angry in travelling space without feeling failure for not achieving a successful travelling identity.